The Effect of Capital Structure, Profitability, and Liquidity on Company Value with Company Size as A Moderation Variable - Oktavia, Sella; Ramadhan, Yanuar (Jurnal Indonesia Sosial Sains, 2024)
This research aims to test whether the structure of capital, profitability, and liquidity affects the value of the company and whether by adding moderation variables the size of the company can strengthen or weaken independent variables against dependent variables.  It is known that the impact of the COVID-19 virus made some banks suffer losses, and others experienced a decrease in profits that lowered the value of the company, one of which is the banking sector. The population used in this study is financial industry companies, namely banking and components which amounted to 34 companies in the period 2020.  The analysis method used in this study uses a multiple linear regression method consisting of independent variables of capital structure, profitability, company size, and moderation variables namely company size, as well as dependent variables i.e. company values.  Based on the results of the F test it was obtained that all independent variables significantly affect dependent variables. Partially, the results that profitability variables have a significant effect on the value of the company, the size of the company strengthens the influence of profitability on the value of the company, and partially also obtained the result that the variables of capital structure, and liquidity do not significantly affect the value of the company, the size of the company weakens the influence of the capital structure, and liquidity on the value of the company. The purpose of the study is to identify and analyze the effect of three main factors, namely capital structure, profitability, and liquidity, on the value of the company.